MASS CONSCIOUSNESS MYTHOLOGIZING: ONTOLOGICAL AND PHENOMENOLOGICAL MEASUREMENTS - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article examines the social, psychological and phenomenological background of modern consciousness mythologizing, its substantial differences from the "traditional" ancient myth-making.